ACOUSTIC MEASUREMENT ON VOWEL PRODUCTION OF ENGLISH AS A SECOND LANGUAGE BY INDONESIAN EFL LEARNERS - Rudha Widagsa; Ahmad Agung Yuwono Putro (University of Kuningan, 2017)
Indonesian is the most widely spoken language in Indonesia. More than 200 million people speak the language as a first language. However, acoustic study on Indonesian learners of English (ILE) production remains untouched. The purpose of this measurement is to examine the influence of first language (L1) on English vowels production as a second language (L2). Based on perceptual magnet hypothesis (PMH), ILE were predicted to produce close sounds to L1 English where the vowels are similar to Indonesian vowels. Acoustic analysis was conducted to measure the formant frequencies. This study involved five males of Indonesian speakers aged between 20-25 years old. The data of British English native speakers were taken from previous study by Hawkins Midgley (2005). The result illustrates that the first formant frequencies (F1) which correlates to the vowel hight of Indonesian Learners of English were significantly different from the corresponding frequencies of British English vowels. Surprisingly, the significant differences in second formant (F2) of ILE were only in the production of /, , / in which //=p 0.002, // =p 0,001, // =p 0,03. The vowel space area of ILE was slightly less spacious than the native speakers. This study is expected to shed light in English language teaching particularly as a foreign language.Keywords: VSA, EFL, Indonesian learners, formant frequencies, acoustic